Economic and Political Foundations of Effective Transition to Renewable Energy: Ordoliberalism, Polanyi, and Cities as Hubs for Climate Leadership and Innovation - Lysack, Mishka (Renewable Energy: International Perspectives on Sustainability, 2019)
A remarkable transition to a renewable energy economy (also known as the Energiewende) with ambitious climate protection and sustainable economic development is taking place in Germany, with many German cities exemplifying best practices in effective climate leadership to attain ambitious climate goals, such as Munich (1.4 million) moving steadily to its targets of 100% renewable energy by 2025 and 100% renewable heat by 2040. Similarly, the former coal city of Bottrop in West Germany won the Innovation Ruhr Prize for increasing its refurbishment rate to 3% (3× national average), installing solar panels, reducing its GHG emissions by 37%, and attracting over $316 million in economic investment in sustainability. However, it needs to be noted these accomplishments do not take place in a vacuum, but within a supportive and empowering policy and economic context which includes two key elements. The first entails using Karl Polanyi’s three key analytic resources of restoring the social and environmental dimensions of the economy: (1) re-embedding the economy within society and in turn, within the larger context of the environment, (2) reversing the reduction of labour and land into “fictitious commodities” and tradable goods; and (3) fostering the “double movements” of the protective responses of both government and society to correct the negative impacts of the free-market economy. Secondly, the economic approach of ordo-liberalism in Germany facilitates the shift to an economy with economic rules and “referees,” fostering the renewable energy transition through innovative economic and social capital approaches, while also deconstructing the economic monopolies and concentrations of political-economic power that arise in neo-liberal and authoritarian economies.
Political Science; Geography
Keywords: double movement; fictitious commodities; ordoliberalism; reembedding; renewable energy economy; sustainability